Promoting Community-based Extension Agents as an Alternative Approach to Formal Agricultural Extension Service Delivery in Northern Ghana - Bonye, Samuel Z; Alfred , Kpieta B; Jasaw, Godfred Seidu (Asian Journal of Agriculture and Rural Development, 2012)
The CBEA concept is an alternative to community-based extension intervention aimed at addressing the inadequacy of formal extension services provision to rural poor farmers of the Northern Regions of Ghana. The study sought to find out the extent to which the Community-Based Extension Agent has improved access to extension services to rural farmers. The study used qualitative and quantitative methods such as, Focus Group Discussions, Key Informants, In-depth interviews, Household and Institutional Questionnaires to collect and analyses data. The findings are that: there are vibrant Community Based Extension Agents established providing extension services in crop, livestock and environmental issues in the study District; farmers groups are linked to external agents and other stakeholders for access to credit facilities; the CBEAs were found to be the main link between the community and external agents; the most dominant extension services delivery carried out by the CBEAs in the entire study district were in crop production, livestock production and bushfire management; there are well established criteria for selecting Community Based Extension Agents, and community Based Extension Agents were least motivated. The study recommends among others that: motivation packages such as bicycles would facilitate the movement CBEAs to reach out to majority of the farmers. There is also the need to link CBEAs to relevant institutions/organizations for support and establishment of mechanisms to generate funds to support activities. Finally, stakeholders and organization need to intensify community sensitization and awareness creation on activities of CBEAs.